Sexual Harassment and Productivity in Erbil City’s Work and Learning Environment: A Case Study - Eiram Amjed Khudhr; Meram Salim Shekh Mohamad; Ala Beshank Ahmed (QALAAI ZANIST JOURNAL, 2024)
This study investigates the relationship between sexual harassment in the workplace and learning environment and its effects on productivity in Erbil city. It explores various dimensions of sexual harassment, including its prevalence, types, and the psychological and emotional toll it takes on victims. Furthermore, it examines how these experiences impact work and learning environment dynamics, job satisfaction, and employee morale. As well as assessing the potential organizational costs associated with sexual harassment, such as less creativity, absenteeism, and decreased overall productivity. Conducting the interview approach to further investigate the victims’ struggles and harassers’ power relations. The study seeks to uncover the extent to which sexual harassment affects employees’ and learners’ ability to perform their tasks effectively. The researchers analyze the findings according to feminist theory on sexual harassment by Bell Hooks and apply Michel Foucault’s theory on power relations. By shedding light on the complex interplay between sexual harassment and productivity, this research aims to provide valuable insights for organizations and policymakers. The findings may help develop strategies to create safer and more productive work environments, ultimately fostering a healthier and more equitable work and learning environment.